Catalyzing and learning from private sector engagement: monitoring to generate evidence and learning - Caldas de Oliveira, Bernardo; Francesconi, Wendy; Rodríguez Sánchez, Beatriz; Deboni, Fabio (2022)
The Catalyzing and Learning through Private Sector Engagement (CAL-PSE) program results from a unique partnership between USAID/Brazil and the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT). The program aims to transform the way we address biodiversity conservation in the Brazilian Legal Amazon, while improving the wellbeing of local communities. By mobilizing the active engagement of the private sector toward implementing sustainable development funding and action, we seek to intensify the involvement of the private sector in the diversification of initiatives aimed at innovating and boosting traditional conservation actions. CAL-PSE has two main lines of activities: engaging the private sector in innovative projects, and creating monitoring and evaluation methodologies that provide clear evidence on the impact of these initiatives on conservation.